Exploring the Potentialities of Special Economic Zones in Nepal - Bhandari, Ramesh (GS Spark: Journal of Applied Academic Discourse, 2023)
Special Economic Zones (SEZs) have been established in many countries around the world as a way to promote economic growth and attract foreign investment. In Nepal, the potential of SEZs has been recognized as a way to boost the economy, but there is a lack of comprehensive research on the potentialities and challenges of establishing SEZs in the country. This study aims to explore the potentialities of SEZs in Nepal by examining the concept of SEZs, the current state of SEZs in Nepal, and the experiences of other countries with SEZs. The study will be conducted using a combination of literature review, data analysis, stakeholder interviews, case studies, and scenario planning. The study will use a combination of literature review, data analysis, stakeholder interviews, case studies, and scenario planning to explore the potentialities of SEZs in Nepal. The findings of the study will provide valuable insights for policymakers and stakeholders in Nepal to support the growth and development of SEZs in the country. The study will also contribute to the larger body of knowledge on SEZs and their role in economic development. In conclusion, the study will provide a comprehensive analysis of the potentialities of SEZs in Nepal and offer recommendations for effective implementation and development. The study will contribute to the understanding of SEZs as a tool for promoting economic growth and attracting foreign investment in Nepal.